Language Errors in Persuasive Speech Texts of Junior High School Students - Tifani Puspa Kristalliana; Gallant Karunia Assidik (Journal La Sociale, 2024)
The persuasive speech material of grade IX students from SMP Negeri 1 Widodaren was examined for grammatical errors. This study examines whether scientific language adheres to standardized principles using a descriptive qualitative analysis. Information is gathered via the process of seeing, documenting, and analyzing. The data revealed that the syntactic errors include both errors in phrase structures and sentence fields. The phrase structure was misused in a total of 9 instances, with 5 mistakes involving inappropriate prepositions, 4 errors involving excessive or redundant elements, 4 errors involving double sharpening, 3 errors involving excessive superlative forms, and 1 error involving wrong arrangement. The sentence field had eight instances of phrase ambiguity errors, four faults involving foreign words, and two errors where predicates were placed incorrectly. The sentence field had a total of 8 instances of ambiguity errors, 4 instances of foreign word mistakes, and 2 instances of predicates-inserted-tear errors. Based on conversations with Indonesian language teachers and many grade IX students, the linguistic errors found in persuasive speech texts for SMP Negeri 1 Widodaren students cannot be attributed to a single reason. The mistakes are caused by internal variables, such as the mastery of the mother language and the correctness of the learner, as well as external ones, such as a lack of vocabulary, comprehension of effective sentences, reading motivation, and a bad class atmosphere.